Cultivating critical reflection: educators making sense and meaning of professional identity and relational dynamics in complex practice. Issue 1 (2nd January 2017) - Morgan, Ann
Abstract: Critical reflection underpins socially just and inclusive practices that are distinguishing features of democratic learning communities. Critical reflection supports educators' interrogation of the underlying assumptions, intentions, values and beliefs that shape their worldview and sociocultural standpoint. Dominant sociocultural norms unwittingly shape the worldview and sociocultural standpoint of educators, which in turn, can contribute to systemic barriers to educational achievement for disenfranchised youth. This paper draws on doctoral research and professional practice with educators in a network of non-traditional flexi schools. The context of flexi schools influences educator identity and development. Much research has highlighted the significance of relational pedagogy as a feature of best practice. However, educators' engagement with critical reflection to enhance the relational dynamics within the learning community requires further research.